2016
DOI: 10.4194/1303-2712-v16_3_29
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: This study was conducted to determine the first maturity size of females of Norway lobster, Nephrops norvegicus (Linnaeus, 1758). Sampling was carried out by commercial trawl in Montenegrin territorial waters (South Adriatic Sea) between summer 2009 and summer 2011 at the depths of 40-350 m. Carapace length of all collected specimen was ranged from 20 to 58 mm CL. The overall females -males sex ratio was 1.4:1. The proportion of mature females in the catch increased from spring to the summer months. The highes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…Marković et al [47] suggested that overfishing was the cause of the decreased size at 50% maturity (25.7 mm CL) observed for N. norvegicus in the South Adriatic Sea, the same size as the one found in the NW Mediterranean. Indeed, the abrupt decline in population abundances, which is observed in the NW Mediterranean Sea, caused by overfishing [4], can be followed by shifts in size and age at first maturity [48][49][50].…”
Section: Discussionmentioning
confidence: 85%
“…Marković et al [47] suggested that overfishing was the cause of the decreased size at 50% maturity (25.7 mm CL) observed for N. norvegicus in the South Adriatic Sea, the same size as the one found in the NW Mediterranean. Indeed, the abrupt decline in population abundances, which is observed in the NW Mediterranean Sea, caused by overfishing [4], can be followed by shifts in size and age at first maturity [48][49][50].…”
Section: Discussionmentioning
confidence: 85%